Simultaneous estimation of retention times of overlapping primary peaks in comprehensive two‐dimensional GC. Issue 17 (9th July 2013) - Zeng, Zhong‐Da; Hugel, Helmut M.; Marriott, Philip J.; Svec, Frantisek
<x xml:space="preserve">Abstract</x> A general approach is developed to estimate the retention time (tR) of overlapping primary peaks in comprehensive 2D GC without assumptions such as the limitation of modulation ratio or symmetry of the target primary peak. Accurate determination of tR can recover the original peak profile by using mathematical fitting. First, the modulation pattern of the first‐dimension peak in the second dimension is summarized with the number of major modulation fractions equal to or less than four. A novel formula to derive tR is defined and separately investigated for cases of modulation number for 1–4, on the basis of the center of gravity of all fractions of the primary peak, in the second dimension. A moving‐window search strategy is further developed for peak clusters overlapping in both separation dimensions, to extract first dimension tR of pure components with the same second dimension time after data pretreatment (background subtraction; time shift correction). Results are very close to the times of simulated comprehensive 2D GC separations. Compared to methods such as reconstruction of original chromatographic profiles to derive tR, the proposed approach balances the precision, and ease of adaption to real applications.